Control of a 1.5 MW active power filter and regeneration converter for a Spoornet DC traction substation - Henning, Pieter Hendrik (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.